Proposed Marketing Strategy of Streaming TV Service to Increase Customer in Bandung City (Case Study: UseeTV Mobile at PT Telkom) - Hapsari, Putri Karima; Purwanegara, Mustika Sufiati (The Indonesian Journal of Business Administration, 2014)
Abstract— Recent fast paced of the technology development, especially in mobile device and broadband technology, has created a new demand about type of entertainment that can be accessed anywhere and anytime. PT Telkom Indonesia, as one of the biggest telecommunication provider in Indonesia, as respond to this new opportunity, developing UseeTV a new streaming entertainment services. UseeTV first launched to the market on August 2012. Although it’s still on introduction, the company has stated a target to have 1 million users on April 2013. But unfortunately, up until the due month the target is still not achieved. Finding the root cause of the problem is important by analyzing 5C method, analyzing the consumer behavior along with analysis of marketing strategy that has been created by the company. The analysis shows that there are three main factors causing the issues: low brand awareness, weak value proposition, and not align product targeting and product offered. To solve the problem, an appropriate and interesting marketing strategy needed. Solutions formulated aim to increase the number of UseeTV users. To overcome problem related to weak value proposition of the service, proposed an increasing on more interesting content according to customers’ needs and wants. Besides, a new STP strategy formulated to develop appropriate marketing strategy. A deeper analysis using factor analysis method is performed to know more about several kinds of factors that could affect customer preference on using the streaming TV services. The discriminant analysis method is also used in this research to know some factors that will differentiate between the streaming TV users who use Usee TV product and those who don’t.  Keywords: streaming, value proposition, brand awareness, factor analysis, discriminant analysis